Accurate and simple determination of oxcarbazepine in human plasma and urine samples using switchable-hydrophilicity solvent in GC-MS - Erarpat, Sezin; Bodur, Suleyman; Ayyildiz, Merve Firat; Gunkara, Omer Tahir; Erulas, Fatih; Chormey, Dotse Selali; Turak, Fatma; Budak, Turkan Borklu; Bakirdere, Sezgin (WILEY, 2020)
This work presents a sensitive and rapid analytical method for the determination of oxcarbazepine in human plasma and urine samples. A vortex-assisted switchable hydrophilicity solvent-based liquid phase microextraction (VA-SHS-LPME) was used to preconcentrate oxcarbazepine from the samples before the determination by gas chromatography mass spectrometry. The switchable hydrophilicity solvent was synthesized by protonatingN,N-dimethylbenzylamine with carbon dioxide to make it totally miscible with an equivalent volume of water. Parameters of the VA-SHS-LPME method including volume of switchable hydrophilicity solvent, concentration/volume of sodium hydroxide and vortex period were systematically optimized. Under the optimum conditions, good linearity ranging from 27.03 to 353.47 mu g/kg was obtained for the analyte. Limit of detection and quantitation values were found to be 6.2 and 21 mu g/kg (mass base), respectively. The relative standard deviation was calculated as 6.9% for six replicate measurements of the lowest concentration of the calibration plot. Satisfactory recovery results were calculated in the range of 97-100% for human plasma and urine samples spiked at five different concentrations.
Keywords: gas chromatography-mass spectrometry; human plasma; oxcarbazepine; switchable hydrophilicity solvent; urine; LIQUID-LIQUID MICROEXTRACTION; 6 ANTIEPILEPTIC DRUGS; PHASE MICROEXTRACTION; SIMULTANEOUS QUANTIFICATION; ELECTROSPRAY-IONIZATION; MASS-SPECTROMETRY; HPLC-UV; CARBAMAZEPINE; CHROMATOGRAPHY; METABOLITES; Biochemistry & Molecular Biology; Chemistry; Pharmacology & Pharmacy